Problematika formaldehida v odpadnih vodah lesne industrije - Muck, Tadeja (Les (Ljubljana), 1999)
Wood industry does not pollute waters to a great extend, nevertheless we must be aware that the problem still exists. Waste effluents in wood industry contain very high portion of dangerous and toxic substance - formaldehyde. That is why it is inevitably vital to start with detailed analysis of waste effluents and with studies of possibilities of decontamination. Statistical analysis are showing that wood industry are not well aware of the fact how quickly the ecological balance can be destroyed, since the quantitiesof treated waste effluents are extremely low. During the seminar some guidelines on how to extract formaldehyde from waste effluents were issued with the stress on secundar method of treatment - biological treatment of waste effluents. Biological treatment can be both, aerobic or anaerobic. During the seminar both methods were introduced with theemphasis on the aerobic procedure, which I was researching in the experimental part of my diploma work.
Keywords: odpadne vode; formaldehid; biološko čiščenje